Organization and Economics of Pharmacy. Chap. 1 "Оrganizational principles of pharmaceutical activities" : educational and methodological guide to practical classes for IV year students specialty 226 «Pharmacy, industrial pharmacy» Professional qualification «Pharmacist» - Tkachenko, N. O.; Lytvynenko, O. V.; Demchenko, V. O.; Mahanova, T. V.; Ткаченко, Наталя Олександрівна; Литвиненко, Ольга Веніаміновна; Демченко, Вікторія Олександрівна; Маганова, Тамара Валеріївна (Запорізький державний медико-фармацевтичний університет, 2025)
The study guide presents educational materials for Section 1 «Оrganizational principles of pharmaceutical activities» in the discipline «Organization and Economics of Pharmacy» (questions for discussion, self-check questions, overview, practical assignments, guidelines for studying the topics of the discipline, self-check tests and a list of references). For training of Masters of Pharmacy in the field 22 «Health care», specialty 226 «Pharmacy, industrial pharmacy», professional qualification «Pharmacist».